Physiological Mechanisms Regulating Lens Transport - Giannone, Adrienne A.; Li, Leping; Sellitto, Caterina; White, Thomas W. (Frontiers in Physiology, 2021)
The transparency and refractive properties of the lens are maintained by the cellular physiology provided by an internal microcirculation system that utilizes spatial differences in ion channels, transporters and gap junctions to establish standing electrochemical and hydrostatic pressure gradients that drive the transport of ions, water and nutrients through this avascular tissue. Ageing has negative effects on lens transport, degrading ion and water homeostasis, and producing changes in lens water content. This alters the properties of the lens, causing changes in optical quality and accommodative amplitude that initially result in presbyopia in middle age and ultimately manifest as cataract in the elderly. Recent advances have highlighted that the lens hydrostatic pressure gradient responds to tension transmitted to the lens through the Zonules of Zinn through a mechanism utilizing mechanosensitive channels, multiple sodium transporters respond to changes in hydrostatic pressure to restore equilibrium, and that connexin hemichannels and diverse intracellular signaling cascades play a critical role in these responses. The mechanistic insight gained from these studies has advanced our understanding of lens transport and how it responds and adapts to different inputs both from within the lens, and from surrounding ocular structures.